Financial Distress dan Managemen Laba pada Industri Jasa Trasportasi di Masa COVID-19 - Salim, Ellionora Novalianti Wongso Sugiarto; Davianti, Arthik (E-Jurnal Akuntansi, 2022)
This study detects financial distress and the existence of earnings management which is classified into accrual and real earnings management in the transportation service industry. The data analysis technique was carried out using Altman's financial distress analysis, followed by linear regression analysis with quantitative descriptive methods. Purposive sampling method was used and the research sample obtained was eight companies with a total of 48 observational data. The results showed that transportation companies at various levels of financial distress were proven to practice accrual earnings management. However, there are differences in the choice of accrual earnings management strategies at each level of distress. In companies that are in advanced distress level, accrual earnings management is carried out by means of income maximization and followed by the practice of big bath. Meanwhile, in extreme distress, the company decides to do income minimization. Keywords:  Financial Distress; Accrual Earnings Management; Real Earnings Management.